PENGEMBANGAN E-BOOK PEMBELAJARAN FISIKA BERBASIS PROBLEM BASED LEARNING (PBL) PADA MATERI POKOK USAHA & ENERGI KELAS X SEMESTER GENAP DI SMA N 3 BINJAI T. A. 2021/2022 - Ramadana, Ahmad; Megalina, Yeni (Universitas Negeri Medan, 2023)
The purpose of this study was to develop an e-book physics learning media based on problem based learning (PBL) using a professional flip pdf on the Business & Energy material and to test the feasibility of the e-book media developed through expert validation and to find out the attractiveness of teacher and student responses. The research and development steps are guided by the 4-D Thiagaraja cycle model (Define, Design, Develop, Disseminate). The develop stage involves two validators to assess the feasibility of the material and media. The Disseminate stage involved 31 students (at SMA N 3, Binjai). The data collection instrument used was a questionnaire with qualitative descriptive data analysis. The results of this study indicate that; (1) The variable of the feasibility test of e-books as learning media by media experts, the overall average score is 100% and by material experts, the overall average score is 98% which belongs to the high category, meaning that e-books developed with professional flip pdf is very feasible to use. (2) The effectiveness variable has an overall average score of 90.93% which is classified in the very effective category, meaning that the e-book is quite effective in helping students increase the value of learning physics in the work & Energy material. (3) The results of the physics teacher response at SMA N 3 BINJAI to the e-book with an overall average score of 88.2% with the Eligibility criteria and product trials for students to respond to the e-book with an overall average score of 86 % with Eligible criteria, it can be concluded that the e-book received a good response from teachers and students.